2021
DOI: 10.14807/ijmp.v12i4.1330
|View full text |Cite
|
Sign up to set email alerts
|

Local companies underperform: a comparative study of industries in Pakistan

Abstract: The capacity of the organization to produce high-quality products at the lowest cost with the fast pace of delivery of goods and services has the potential to determine the survival, sustainability, and growth of organizations in emerging globalization and competition. The researcher has critically examined the impact of people's development, employee welfare, leadership effectiveness, and Human Resources operations effectiveness in the context of local, Multinational Companies, and public sector organizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Based on the differences in the cross-cultural management model, a 5-year study on I after the acquisition of the business management model found that the corporation adopted the cultural management model using the second model after the acquisition, gradually transitioning to the first three models before finally reaching the first mode (Uzyumova, 2019). In order to reflect the goal of management research on the alienation of the I company, this study uses the management toolbox principle of the I company (Kazi and Chandani, 2021) as a cross-cultural management tool and cultural intermediary variable to express the significance of corporate values and culture (Song et al, 2020). To design the vouchers, Odukoya et al (2020) suggested that the questionnaire use the level of recognition and use the toolbox to represent the degree of corporate cultural identities of employees in cross-cultural management and to conduct hypotheses of mediating effects.…”
Section: Cross-cultural Management Intermediary Variations: Toolbox Management Methods Of I Enterprisesmentioning
confidence: 99%
“…Based on the differences in the cross-cultural management model, a 5-year study on I after the acquisition of the business management model found that the corporation adopted the cultural management model using the second model after the acquisition, gradually transitioning to the first three models before finally reaching the first mode (Uzyumova, 2019). In order to reflect the goal of management research on the alienation of the I company, this study uses the management toolbox principle of the I company (Kazi and Chandani, 2021) as a cross-cultural management tool and cultural intermediary variable to express the significance of corporate values and culture (Song et al, 2020). To design the vouchers, Odukoya et al (2020) suggested that the questionnaire use the level of recognition and use the toolbox to represent the degree of corporate cultural identities of employees in cross-cultural management and to conduct hypotheses of mediating effects.…”
Section: Cross-cultural Management Intermediary Variations: Toolbox Management Methods Of I Enterprisesmentioning
confidence: 99%
“…Employee retention strategies in shaping employee commitment often use their knowledge and skills to benefit the organization (Harris, 2019;Parmar et al, 2019); this was by Herzberg's two-factor theory to help explore and understand positive employee behavior (Alrawahi et al, 2020;Kazi & Chandani, 2021). Effective training and opportunities for learning and development can improve employee retention (Arnold, 2005;Gupta et al, 2021;Herman, 2005;Hiltrop, 1999).…”
Section: Introductionmentioning
confidence: 99%